Spatial memory - a unique window into healthy and pathological ageing - Emma R. Wood (Frontiers Research Topics, 2015)
The global population aged over 60 is set to rise dramatically in the coming decades. In many countries, the older population now faces the prospect of spending a quarter of their lives aged over 65, and a significant proportion will have to cope with cognitive decline associated with normal ageing or with dementia disorders. Given that these fundamental demographic changes will pose a significant challenge to health care systems, a detailed understanding of age-related cognitive and neurobiological changes is essential in helping elderly populations maintain cognitive performance. In addition, developing sensitive biomarkers to identify those at risk of developing dementia is crucial for early and effective interventions. To make inferences about the ageing process from the animal model back to the human, rigorous behavioral paradigms must be used to ensure that the same function is being examined across species. Given that similar navigational paradigms can easily be applied to humans and animals, recent years have seen an expansion of studies attempting to bridge the gap between age-related changes in animal and human spatial cognition. These studies begin to suggest that disruptions in spatial computations are among the earliest indicators of impending cognitive decline. In addition, although many animal studies have identified pathological mechanisms with paradigms involving spatial navigation, these mechanisms support many nonspatial cognitive functions as well. As a consequence, a successful characterization of how spatial processing changes in the ageing brain could reveal fundamental effects of cognitive ageing that could inform about general mechanisms underlying decline in perception, mnemonic processing and multisensory integration.